EXAMINATION OF PARENTAL INVOLMENT ON UPPER PRIMARY PUPILS PARTICIPATION IN ACADEMIC ACTIVITIES IN PUBLIC SCHOOLS IN LAIKIPIA WEST SUB-COUNTY, LAIKIPIA COUNTY, KENYA - Romata, Samuel; Adhiambo , Jacinta; Getui , Mary (Journal of Education and Practice, 2021)
Purpose: The study aimed at finding out whether parents in public primary schools in Laikipia West sub-county influence pupils to participate in academic activities. Methodology: A mixed method research design was used where cross sectional descriptive survey was used on quantitative data and phenomenology was used to complement components of qualitative data. Population of 13 public Primary schools was sampled from the total 65 public Primary Schools in the Sub-County. Out of 2,236, pupils' in class 6, 7 and 8, 3 girls and 3 boys were selected per class through stratification and simple random method. Parents/ guardians for the selected pupils were purposively selected regardless of their age, level of education and gender. All class teachers from the sampled schools were targeted and purposively selected. The data was collected using questionnaires, interview guide, document analysis guide and focus discussion guide. Statistical Package for Social Sciences (SPSS) version 17 was used to analyze quantitative data. Nine hypotheses that sought to find out parental influence on pupils' participation in academic activities were tested using correlation coefficient analysis. Qualitative data was transcribed, coded, and themed and interpreted in response to research questions. Results: The results from the study showed that there is prevalence of parental influence on pupil's academic activities in Laikipia West Sub- County mainly through attending school functions, assisting with homework, communicating with teachers and their children and provision of learning resources. In response to parental involvement, pupils attended school regularly; asked questions in class, joined study groups and finished homework on time. Major restrictions to parental involvement included poverty, insecurity and illiteracy. Unique Contribution to Theory, Practice and Policy: The recommendation was that those parents who were not actively involved on pupil's academic related matters be sensitized on their roles of promoting child education. The County as well as national governments should support parents by establishing structures and policies that boost the standard of education in the area. According to this study such policies includes; establishing efficient and effective guidance and counseling programs in school, taking legal action on parents who keep their children at home, providing full sponsorship to needy parents and establishing boarding schools among the pastoralists communities.